Demyelinating steroid-responsive neurobrucellosis. Issue 3 (8th March 2020) - Ata, Fateen; Yousaf, Zohaib; Sharif, Mohammad Khalid; Abdallah, Ahmed
Abstract : Young man with acute onset nausea, vomiting, joint pain, abdominal pain, fever and weight loss was found to have gait ataxia and positive B rucella titres. He deteriorated despite appropriate antibiotics and developed confusion and disorientation. Lumbar puncture revealed lymphocytosis with high protein and low glucose. MRI showed diffuse demyelination. Pulse steroids resulted in rapid clinical, biochemical and radiological recovery.